(Z)-N-[(Z)-3-(2,5-Dimethylphenylimino)butan-2-ylidene]-2,5-dimethylaniline - Lv, Wen-Xian (International Union of Crystallography, 2014)
The asymmetric unit of the title compound, C20H24N2, contains one half-molecule, with the single C—C bond of the 1,4-diazabutadiene fragment situated on a centre of symmetry. The benzene rings are inclined to the 1,4-diazabutadiene mean plane by 59.5 (1)°.